Interventions to reduce stigma related to people who use drugs: systematic review - Tostes, Joanna Gonçalves de Andrade; Dias, Rafaela Toledo; Reis, Andressa Aparecida da Silva; Silveira, Pollyanna Santos da; Ronzani, Telmo Mota (Paidéia (Ribeirão Preto), 2020)
Interventions to reduce stigma related to people who use drugs can improve their quality of life and adherence to treatment. This review aimed to identify and analyze studies on interventions to reduce the stigma related to people who use drugs. Searches were performed in the following databases, without period delimitation: PubmMed, APA PsycNET, ScienceDirect, Web of Science, and VHL. Considering secondary referencing, we identified a total of 5,488 records. This review covered 28 articles and was based on PRISMA. Although target audiences comprising students and health professionals were predominant, as well as the use of quantitative methods, sample size and interventions varied among studies. The selected studies present considerable methodological limitations. We concluded that no evidence confirms the effectiveness of the proposed interventions and which of them should continue to be applied for this specific aim. It is essential to invest in approaches other than those traditionally adopted.